1996
DOI: 10.1088/0953-2048/9/4/006
|View full text |Cite
|
Sign up to set email alerts
|

The effects of composition, synthesis conditions, oxygen content and F doping on superconductivity and structure for R-substituted Bi-2201

Abstract: The effects of composition, synthesis conditions, oxygen content and F doping on superconductivity and structure for the R-substituted Bi-2201 compound was investigated by means of XRD and measurements of superconductivity. For the Bi 1.95 Sr 2.05−x R x CuO 6+y compound (R = La, Pr, Nd and Sm), the optimum value of x for T c is x = 0.4. When x = 0.4, the optimum sintering temperature is 840 • C for R = La, Pr and Nd, 820-830 • C for R = Sm. T c decreases with decreasing the ionic radius of R. For Bi 1.95 Sr 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Previous studies reported that the T c of Bi-2201 is about 6-10 K in a very narrow range of Bi:Sr ratio [1]. Partial substitution of Sr by large atomic radius rare-earth elements such as La or Nd expands the superconducting range and also increases T c to 24-35 K [2,3]. When added La, the BiSrLaCuO system easily becomes superconducting, and the optimum substitution of La for Sr was shown to be 0.4 [4,5].…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies reported that the T c of Bi-2201 is about 6-10 K in a very narrow range of Bi:Sr ratio [1]. Partial substitution of Sr by large atomic radius rare-earth elements such as La or Nd expands the superconducting range and also increases T c to 24-35 K [2,3]. When added La, the BiSrLaCuO system easily becomes superconducting, and the optimum substitution of La for Sr was shown to be 0.4 [4,5].…”
Section: Introductionmentioning
confidence: 97%